2021
DOI: 10.1021/acssuschemeng.0c08483
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Determination of the Role of Aluminum in Particle Adhesiveness at High Temperatures Induced by Sodium and Potassium Using a Synthetic Ash Strategy

Abstract: Energy recovery from various fuels with high efficiency is an important objective to realize sustainable energy conversion systems. During the combustion process, ash particles are produced that can form aggregates inside of combustion plants, which inhibit stable and effective plant operation. This is a serious problem for plant operation, and the control of ash particle aggregation under high-temperature conditions is an important objective. In this research, a method to effectively suppress the adhesiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…A device to evaluate the adhesiveness of particles at high temperatures was developed previously and could measure the adhesiveness of many types of particulate materials, including combustion and incineration ashes. An analysis of various ashes revealed that P, Na, and K in ashes increased adhesiveness at high temperatures. For sewage sludge incinerated ashes, which contained P at high concentrations, adhesiveness began to increase near 600 °C, a temperature that is lower than that of coal ashes. , This observation indicated that the adhesiveness of ashes that contain P easily adhere inside the incineration machinery. These provided a promising method for quantifying the adhesiveness of P-containing ashes at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A device to evaluate the adhesiveness of particles at high temperatures was developed previously and could measure the adhesiveness of many types of particulate materials, including combustion and incineration ashes. An analysis of various ashes revealed that P, Na, and K in ashes increased adhesiveness at high temperatures. For sewage sludge incinerated ashes, which contained P at high concentrations, adhesiveness began to increase near 600 °C, a temperature that is lower than that of coal ashes. , This observation indicated that the adhesiveness of ashes that contain P easily adhere inside the incineration machinery. These provided a promising method for quantifying the adhesiveness of P-containing ashes at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Because the chemical components of ashes are complex, the detailed roles of the different elements in adhesiveness are unclear. To clarify the effect of each element in ash on adhesiveness, a strategy using synthetic ash was developed to understand the role of an element in adhesiveness at high temperatures. , Synthetic ashes consist of base particulate materials that are stable and target elements that induce adhesiveness at high temperatures. In a simple synthetic ash system, the role of target elements in adhesiveness can be determined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have been engaging in research on fly ash deposition using a tensile strength tester (Figure ). The tester can directly measure the tensile strength of fly ash powder beds that are closely related to the interparticle adhesion. Most importantly, the tester can predict fly ash deposition that occurs at temperatures significantly lower than the ash melting point, where no significant liquid (slag) phase formation is expected.…”
Section: Introductionmentioning
confidence: 99%